Recent Research Activities in Solid and Liquid Bioenergy from Lignocellulosic Biomass - Jae-Hyuk Jang; Seung-Hwan Lee; Nam-Hun Kim (Wood Research Journal, 2015)
The increase in energy demand, the lack of petroleum resources, and concern over global climate change have placed great emphasis on the development of new alternative energy technologies that can be used to replace fossil transportation fuels (Himmel et al. 2007; Labbe et al. 2008; Lee et al. 2009a,b,c; Teramoto et al. 2008, 2009). In this context, many countries have initiated extensive research and development programs for bioenergy. Bioenergy can be classified into three kinds of solid, liquid, and gas bioenergy. For the effective production and utilization of these three types of bioenergy, different technologies are required (Figure 1). Lignocellulosic biomass, such as wood and agricultural residues, are widely distributed and easily accessible at relatively low costs. Of these, wood has the benefit of having a higher energy content per volume, lower ash content, and nitrogen content. In this review, recent research trends and advances in bioenergy from lignocellulosic biomass will be summarized from the author’s point of view.